2015 IEEE International Symposium on Systems Engineering (ISSE) 2015
DOI: 10.1109/syseng.2015.7302802
|View full text |Cite
|
Sign up to set email alerts
|

Active learning via LEGO MINDSTORMS in Systems Engineering education

Abstract: The education of Systems Engineers involves many learning aspects that cannot be taught through lecturing alone, such as how to handle unforeseen issues and establish a holistic view of a system. An educational approach is presented that allows students to experience key phases of a Systems Engineering lifecycle, from requirements and design to system realisation and test, by using LEGO® MINDSTORMS® as an active learning tool. The approach is evaluated based on student feedback and is shown to be an effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
4
0
1
Order By: Relevance
“…Moreover, the students perceived positive outcomes regarding the development of their soft skills (4.55), which are critical in their professional career [32]. These results regarding LSP benefits are consistent with those obtained in other fields including marketing [18], arts [19], education [20], civil engineering [21], industrial engineering [22], and systems engineering [23].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Moreover, the students perceived positive outcomes regarding the development of their soft skills (4.55), which are critical in their professional career [32]. These results regarding LSP benefits are consistent with those obtained in other fields including marketing [18], arts [19], education [20], civil engineering [21], industrial engineering [22], and systems engineering [23].…”
Section: Discussionsupporting
confidence: 70%
“…In the last years, it has been used in higher education contexts in fields such as marketing [18], arts [19] or education [20]. LSP has also been used in engineering education, for example, in civil engineering [21], industrial engineering [22] or systems engineering [23]. These contributions report very positive outcomes regarding the student's learning process including aspects such as development of ideas and products, the identification of risks and responsibilities, and the communication and cooperation abilities.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…O principal motivo da enorme popularidade do kit é a sua facilidade de compreensão e sua curva de aprendizagem rápida que está relacionada com a programação em blocos que se encaixam similar a ideia do hardware do kit. O dispositivo permite com que iniciantes na área da robótica aprendam sobre design e desenvolvimento de forma eficaz [18]. O grande diferencial deste kit para os demais apresentados no mercado é a junção dos blocos de montar bastante conhecidos com a possibilidade de montar quase o que a imaginação do usuário permitir com atuadores, sensores e um microcontrolador programável que possibilita o desenvolvimento de vários robôs em um só kit.…”
Section: Trabalhos Relacionados Ao Pensamento Computacionalunclassified
“…For several years' practice on this subject, we found that the students dislike the course. So we try to reform this experimental course [1,2].…”
Section: Introductionmentioning
confidence: 99%